A Putative Multisubunit Na(+)/H(+) Antiporter from Staphylococcus aureus - Hiramatsu, Toshiaki (American Society for Microbiology, 1998)
We cloned several genes encoding an Na(+)/H(+) antiporter of Staphylococcus aureus from chromosomal DNA by using an Escherichia coli mutant, lacking all of the major Na(+)/H(+) antiporters, as the host. E. coli cells harboring plasmids for the cloned genes were able to grow in medium containing 0.2 M NaCl (or 10 mM LiCl). Host cells without the plasmids were unable to grow under the same conditions. Na(+)/H(+) antiport activity was detected in membrane vesicles prepared from transformants. We determined the nucleotide sequence of the cloned 7-kbp region. We found that seven open reading frames (ORFs) were necessary for antiporter function. A promoter-like sequence was found in the upstream region from the first ORF. One inverted repeat followed by a T-cluster, which may function as a terminator, was found in the downstream region from the seventh ORF. Neither terminator-like nor promoter-like sequences were found between the ORFs. Thus, it seems that the seven ORFs comprise an operon and that the Na(+)/H(+) antiporter consists of seven kinds of subunits, suggesting that this is a novel type of multisubunit Na(+)/H(+) antiporter. Hydropathy analysis of the deduced amino acid sequences of the seven ORFs suggested that all of the proteins are hydrophobic. As a result of a homology search, we found that components of the respiratory chain showed sequence similarity with putative subunits of the Na(+)/H(+) antiporter. We observed a large Na(+) extrusion activity, driven by respiration in E. coli cells harboring the plasmid carrying the genes. The Na(+) extrusion was sensitive to an H(+) conductor, supporting the idea that the system is not a respiratory Na(+) pump but an Na(+)/H(+) antiporter. Introduction of the plasmid into E. coli mutant cells, which were unable to grow under alkaline conditions, enabled the cells to grow under such conditions.